Dem bones - Barner, Bob. (San Francisco : Chronicle Books, 1996)
Factual information about the bones in the body is presented in the course of a rendition of the traditional African spiritual, "Dem Bones.".
Book Links (A.L.A.)
School Library Journal
Wilson's Children
3.8
K-3.
K-3
Keywords: Bones -- Juvenile literature; Human skeleton -- Juvenile literature; Bones; Skeleton; Bones; Skeleton